Der Einfluss der elterlichen Trennung im Jugendalter auf die Depressivität von Jugendlichen - Michael Feldhaus; Andreas Timm (Journal of Family Research, 2015)
This paper investigates the relationship between parental divorce and the occurrence of depressive symptoms in adolescents, with a particular focus on the quality of parent-child relationships. We use data from the youth cohort (15-17 years old at the time of the first interview) of the first four waves of the Panel Analysis of Intimate Relationships and Family Dynamics (abbreviated as pairfam). Panel regressions models, such as fixedeffects models and so-called hybrid models are applied to analyze the causal effects of parental divorce. Our results confirm previous research, in particular from English-speaking countries, that parental divorce or separation increase depressive symptoms significantly. This effect is particularly relevant in high-conflict relationships between children and their mother and father, respectively, while in parent-child relations characterized by high levels of intimacy the negative effects are considerably reduced.